Numerical Analysis of Aneurysm in Artery - Bai, H. Girija (International Journal of Psychosocial Rehabilitation, 2020)
In this article, the numerical solution of blood vessels affected by aneurysm with dilation 25% is analyzed. Hemodynamic factors such as pressure and velocity are computed using Finite Volume Method. High pressure and low velocity is observed in the region of aneurysm. This is a sign to the disruption of blood flow. To understand the relationship between hemodynamic parameters and risk of rupture computational methods plays a vital role.